2022
DOI: 10.3389/fenvs.2022.1044921
|View full text |Cite
|
Sign up to set email alerts
|

Biochar enhanced phytostabilization of heavy metal contaminated mine tailings: A review

Abstract: Mining activities has generated large amounts of mine tailings each year, and these tailings usually contain high concentrations of heavy metal pollutants, which not only cause serious damage to the local and surrounding soil ecosystems, but also harm human health via the transmission of food chain. Phytoremediation is treated as environmentally friendly, long-term effective and low-cost restoration method. However, tailing soil acidification, low organic matter content, poor water holding capacity and compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…The BC further reduced heavy metal concentrations beyond the effect of lime, as indicated by reduced Zn with 0.5% lime in Experiment 2 (Figure S6). BC was shown in several studies to decrease available heavy metals in soils (Ippolito et al., 2019; Phillips et al, 2016; Shi et al., 2022). In addition, the increase in needle K with BC (Figure 4) confirmed that BC also can provide certain essential plant nutrients, especially K (Wang et al., 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The BC further reduced heavy metal concentrations beyond the effect of lime, as indicated by reduced Zn with 0.5% lime in Experiment 2 (Figure S6). BC was shown in several studies to decrease available heavy metals in soils (Ippolito et al., 2019; Phillips et al, 2016; Shi et al., 2022). In addition, the increase in needle K with BC (Figure 4) confirmed that BC also can provide certain essential plant nutrients, especially K (Wang et al., 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Also, Trichoderma, a type of soil fungus, can bond to soil particles by mycelium or act as a binding agent in soil particles by secreting insoluble extracellular substances. This action improves the soil's Porosity and water-holding capacity (Shi et al, 2022).…”
Section: Available Water Content (Awc)mentioning
confidence: 99%
“…This can be attributed to the high-water retention and less oxygen in the pore space leading to an anaerobic state of the plant roots. Also, the high adsorption capacity at the early stages, reduces the release of nutrients thereby leading to lack of fertilisers in the later stages (Shi et al, 2022).…”
Section: Translocation and Bioconcentration Of Heavy Metals Biochar A...mentioning
confidence: 99%